1981
DOI: 10.1538/expanim1978.30.3_313
|View full text |Cite
|
Sign up to set email alerts
|

Carrier State of <I>Pasteurella pneumotropica</I> in Mice and Rats

Abstract: Localizationof Pasteurella pneumotro pica was investigated in the respiratory tract, conjunctiva and vagina of 5-week-old, 10-week-old and retired asymptomatic mice and rats.The highest isolation rate of the organisms was obtained in the pharyngolarynx, showing 85 to 97.5% in carrier mice and 100% in carrier rats. Numbers of the organisms in this site were 103-5 and 107-8 organisms/g tissue in 4-week-old mice and rats, respectively. Isolation rates in the nasal cavity and trachea of the both animals were not s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
14
0

Year Published

1983
1983
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 4 publications
1
14
0
Order By: Relevance
“…Pathogen status of laboratory mice and rats in this country has been extensively examined these 10 years by several investigators [3,4,14,16] Swab samples of the external nares and trachea including pharyngo-larynx area were cultured on blood agar, DHL agar (Eiken Co., Tokyo) and PPLO agar for detection of P. pneumotropica [11], B. bronchi septica [9] and M. pulmonis [12], respectively.…”
mentioning
confidence: 99%
“…Pathogen status of laboratory mice and rats in this country has been extensively examined these 10 years by several investigators [3,4,14,16] Swab samples of the external nares and trachea including pharyngo-larynx area were cultured on blood agar, DHL agar (Eiken Co., Tokyo) and PPLO agar for detection of P. pneumotropica [11], B. bronchi septica [9] and M. pulmonis [12], respectively.…”
mentioning
confidence: 99%
“…The main colonization sites of P. pneumotropica in the latently infected mice are propably upper respiratory, intestinal and genital tracts [6,11]. However, distribution of the organism in the intestine was not clear, because isolation of the organism from the intestinal samples with conventional media is difficult [11].…”
Section: Discussionmentioning
confidence: 99%
“…However, distribution of the organism in the intestine was not clear, because isolation of the organism from the intestinal samples with conventional media is difficult [11]. We have therefore developed the selective media, and successfully isolated the organism from the intestinal tract and feces [6].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is well known that mice and rats are often healthy carriers of the organism [4,5,7,8,13,17,18], however, host-specific parasitism of the organism has not yet been investigated except our previous study in which rat strains were shown to be inf ective to rats but rarely to mice, while mouse strains were highly inf ective to both animals [12].…”
mentioning
confidence: 99%